Incidence and mortality for cutaneous squamous cell carcinoma: comparison across three continents. (13th December 2019) - Stang, A.; Khil, L.; Kajüter, H.; Pandeya, N.; Schmults, C.D.; Ruiz, E.S.; Karia, P.S.; Green, A.C.
Abstract: Background: Population‐based incidence and mortality studies of cutaneous squamous cell carcinoma (SCC) have been few owing to the commonness of the disease, and rare deaths making accurate mortality statistics difficult. Objectives: Our aim was to summarize SCC incidence and mortality in populations across three continents, exemplified by Australia, the United States (US) and Germany. Methods: We estimated age‐specific and age‐standardized (Australian Standard 2001 Population) incidence and mortality rates per 100 000 person‐years. Results: Squamous cell carcinoma incidence is plateauing or falling in Australia, stable in the United States (2013–2015) and rising in Germany (2007–2015). Current incidence estimates in men and women are 341 and 209, 497 and 296, and 54 and 26, respectively, for the three countries. Incidence increases strongly with age in all countries. Mortality of non‐melanoma skin cancer appears to be increasing in Germany and stable in Australia (unavailable for the US population). Conclusions: Squamous cell carcinoma is an important health issue, particularly among older men, with incidence exceeding most other cancers. More precise and uniform population‐based studies of incidence and mortality are needed to better quantify the impact of SCC on healthcare systems worldwide and to gauge the effect of new treatments such as anti‐PD1 therapy on mortality.